(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
The paper presents the assessment of the electric output rendered by a unimorph and a bimorph piezoelectric harvester, with one and respectively two active piezoceramic wafers, by means of numerical simulations. Expected sinusoidal voltages were obtained in time dependent study, with a time step corresponding to the eigenfrequency found after conducting an Eigenfrequency study. The terminal voltages obtained are in agreement with Euler-Bernoulli beam theory and with the distance of the piezoelectric layers from the neutral fibre. If Electrical Circuit physics is to be added to form a closed internal circuit, a single unified sinusoidal voltage response should be obtained, coinciding with the input vibration signal. The independent voltages of the layers of a piezoelectric structure with more than one layer (usually two or four layers) cannot be observed experimentally, as a harvester has only two terminals which pick the overall electric response from all the layers, giving a single alternating voltage output.